Between Potential and Environmental Influences for Individual Success: A Review from An Educational Perspective - Abidin, Dindin; Aminudin, Muhammad Sulton; Supriatna, Eka; Alvinuri, Kaf Kaffah; Ramadhan, Iwan (LP. Ma'arif Janggan Magetan, 2024)
The purpose of this study is to investigate the low level of student motivation in the learning process and its potential impact on their future success. The factors that affect the learning process are not limited to the students themselves, but also external factors. The factors that affect the learning process are not limited to the students themselves, but also include external factors. The relationship between these factors is crucial, as an unstable balance between them can hinder the learning process and lead to suboptimal results. The objective of this research is to investigate the impact of school and family environments, as well as the role of teachers, on students' learning motivation. A literature review was conducted to achieve this objective. The results indicate that both the school environment and the role of the teacher have a significant positive influence on students' motivation to learn, which in turn leads to individual success.